2022
DOI: 10.48550/arxiv.2203.09198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Paper: AWAKE, Plasma Wakefield Acceleration of Electron Bunches for Near and Long Term Particle Physics Applications

Abstract: Plasma-based accelerators have made remarkable progress over the last two decades. Their unique characteristics make them tools that can revolutionize fields of science and applications. AWAKE takes advantage of the availability of high-energy, relativistic proton bunches to drive large amplitude wakefields (∼GV/m) in a single plasma over distances sufficient to produce hundreds of GeV to TeV electron bunches. Hundreds of GeV bunches with O(10 9 ) electrons could replace current electron sources based on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…With sufficient science motivation, one possible IEF that could be considered is a 20-100 GeV center-of-mass energy ANA-based linear lepton collider. In what follows we focus on the science case for an IEF since the necessary R&D effort as well as potential near term applications of ANAs are outlined in other white papers submitted to Snowmass21 [6][7][8]. The goal of the proposed IEF is to both carry out particle physics measurements in the 20-100 GeV ranges, as well as to serve as a ANA demonstrator facility.…”
Section: Jinst 19 T01010mentioning
confidence: 99%
See 1 more Smart Citation
“…With sufficient science motivation, one possible IEF that could be considered is a 20-100 GeV center-of-mass energy ANA-based linear lepton collider. In what follows we focus on the science case for an IEF since the necessary R&D effort as well as potential near term applications of ANAs are outlined in other white papers submitted to Snowmass21 [6][7][8]. The goal of the proposed IEF is to both carry out particle physics measurements in the 20-100 GeV ranges, as well as to serve as a ANA demonstrator facility.…”
Section: Jinst 19 T01010mentioning
confidence: 99%
“…Electron beams have been accelerated up to 8 GeV over 20 cm at the Lawrence Berkeley National Laboratory using a PW laser pulse propagating in a plasma channel [5]. A discussion of the status of ANA research as well as the necessary avenues for achieving progress in this field may be found in the whitepapers "Linear collider based on laser-plasma accelerators", "AWAKE, Plasma Wakefield Acceleration of Electron Bunches for Near and Long Term Particle Physics Applications", and "Near Term Applications driven by Advanced Accelerator Concepts" submitted to Snowmass21 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%